A review study on common injuries in field hockey players - Leelavathy, M. J.; Madhu, G. R. (International Journal of Physiology, Nutrition and Physical Education, 2021)
This article outlines the most common injuries suffered by female field hockey players. Hockey is a centuries-old sport that is regarded to be the ancestor of all 'stick and ball' activities. The modern game of hockey is played in 132 nations worldwide and is second only to soccer in terms of popularity as a team sport. The injury could be fatal, leaving you disabled for the rest of your life. Injuries may have long-term consequences, as there is evidence that knee and ankle injuries may raise the incidence of osteoarthritis later in life. Although it is difficult to eradicate all injuries, efforts to decrease them are clearly required by coaching and coaching competence. Different research utilized different classifications for injury severity, however injuries were typically included in the less severe group within studies. Sprain, strain, dislocation, lower back pain were the most common type injuries in field hockey players.